2009
DOI: 10.1016/s0924-9338(09)70664-9
|View full text |Cite
|
Sign up to set email alerts
|

Low Emotional Intelligence as a Predictor of Tendency to Addiction

Abstract: Aim:The study is to clarify role of emotional intelligent in addicted and nonaddicted people.Method:80 addicted and 82 nonaddicted people were randomly selected and Schutte's Self- Report Emotional Intelligence Test (SSREIT) administered on them. Data were analyzed with independent T formula.Results:Results showed significant differences between components of emotional intelligent especially in regulation, expression and assessment of emotions between tow groups.Discussion:Findings indicates that applying of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2012
2012
2016
2016

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 0 publications
0
3
0
1
Order By: Relevance
“…Depuis les années 90, les travaux sur l’IE se multiplient, tant concernant sa conceptualisation et son opérationnalisation 2,5 –8 , que dans le champ du management et des ressources humaines 9 , de l’éducation 10 , ou l’étude de son rôle sur la santé et le bien-être 11 et la psychopathologie. Dans le domaine de la santé mentale, plusieurs travaux ont rapporté un déficit d’IE chez des patients présentant des pathologies psychiatriques comme les troubles de la personnalité 12,13 , les troubles anxieux et dépressifs 14 , les pathologies addictives 11,15,16 et troubles des conduites alimentaires, dont l’anorexie mentale 17 et la boulimie 18,19 .…”
Section: Limitesunclassified
“…Depuis les années 90, les travaux sur l’IE se multiplient, tant concernant sa conceptualisation et son opérationnalisation 2,5 –8 , que dans le champ du management et des ressources humaines 9 , de l’éducation 10 , ou l’étude de son rôle sur la santé et le bien-être 11 et la psychopathologie. Dans le domaine de la santé mentale, plusieurs travaux ont rapporté un déficit d’IE chez des patients présentant des pathologies psychiatriques comme les troubles de la personnalité 12,13 , les troubles anxieux et dépressifs 14 , les pathologies addictives 11,15,16 et troubles des conduites alimentaires, dont l’anorexie mentale 17 et la boulimie 18,19 .…”
Section: Limitesunclassified
“…Furthermore, other mediating variables (risk factors) such as low intelligence (Khanmohammadi, Homayouni, Amiri, & Nikpour, 2009), low emotional intelligence (Kun & Demetrovics, 2010) dysfunctional family environment and early trauma (Ciarrocchi & Hohmann, 1989) should also be taken into consideration as etiological factors, none of which has been tested in connection to compulsive buying before. Finally, common underlying neurobiological proneness should also be taken into consideration (Trull et al, 2000).…”
Section: Future Directionsmentioning
confidence: 99%
“…They reported that the adolescents with high EI could possess a greater mental ability to read others well and detect unwanted peer pressure. Khanmohammadi et al (2009) reported that applying of some plans in the field of increasing emotional intelligence could help people with positive attitudes to addiction to manage the bad problems and event and as a result reduce tendency to addiction. Talebzadeh and Homayouni (2010) performed a survey on relationship between emotional intelligence and personality traits in addicted people.…”
Section: Introductionmentioning
confidence: 99%